"Numbers, too, have significance": Annotating Salman Rushdie. (March 2017) - Mishra, Vijay
Strictly speaking, annotations do not belong to the discipline of bibliography, that is, if we follow its reading by three of the masters of the discipline: Ronald B. McKerrow, W. W. Greg and Fredson Bowers. Bibliography, in their definitions, is a scientific activity aimed at the construction of text as a "material" object. It has guiding principles that govern the quest for the "definitive" text where words are primarily iconic or indexical signs. To gloss words and sentences in support of a variant reading is a necessary evil, not something which is part of its formal principles. If textual bibliography were to accommodate some notion of annotations, as "bibliograhie de l'érudit", then we need to make a case for annotation as an essential feature of the bibliographer's exercise. This essay declares the legitimacy of annotation because it establishes the value of words well beyond the iconic or the indexical (the hitherto definition of the bibliographer's object of reading). To explore this the article examines the use, in particular, of "numerology" in Salman Rushdie, annotates at length four numbers, and makes a case for their value in the organizational and thematic patterns of his novels. It is argued that numbers are also part of Rushdie's interest in "affects" insofar as for Rushdie numbers are prior to cognition, they pre-exist consciousness and are not so much created as discovered. They also enter into the affective domain of being and are signs of the body's visceral intensities as well as an index of its nonvolitional proclivities. In making the annotations the essay also explores the importance of intercultural annotations by giving the example of pre-colonial Indian scholarship.